Clinical and hematological profile of anemia in children aged 6 months to 12 years at tertiary care hospital in central India - Choudhary, Priyanka; Kumar, Saurabh; Ambhore, Jaishree (International Journal of Contemporary Pediatrics, 2021)
Background: Anemia is a major global health problem. It results in significant morbidity and mortality among children. Methods: It is a retrospective study carried out with the help of medical records of Chirayu Medical College and Hospital Bhopal, from January 2017 to December 2019. Total number of 138 cases were taken in study as per inclusion criteria. Anemia was diagnosed on the basis of hemoglobin level and age of presentation. Anemia was classified into different types as per different hematological parameters and other relevant investigations. Results: Out of 138 children, 96 were found to be anemic. Majority of children were of age group 1 year to 5 years. There was male preponderance. It was found that 57% of children were anemic due to iron deficiency anemia, 16% were having thalassemia, 11% were having megaloblastic anemia, 5% with sickle cell anemia and 2% with aplastic anemia. Conclusions: Iron deficiency anemia is a major cause of morbidity worldwide. Anemia control is a global priority. Strategies to combat anemia by forging public private partnership, iron supplementation program, iron fortification of food items (point of care and at the level of manufacturing) and dissemination of awareness regarding anemia and treatment should be implemented. Special care should be taken to diagnose and counsel other major causes of anemia like thalassemia depending on the endemicity.